a Prediction Of Crop Monitoring Indices ( NDVI,MSAVI,RECI) And Estimation Of Nitrogen Concentration On Leaves For Possible Of Optimizing the Time of Harvest With the Help of Sensor Networks In Guntur Region ,Andhra Pradesh , India. With agent based modeling - Rajarammohanrao Karnati; M.V.S PRASAD (International Journal of Advanced Science and Computer Applications, 2023)
This paper shows the utility of natural sensors for the observing of crop from a distance in a greenhouse. The work joins the instrumentation methods with the information-based framework. Agriculturalists can know the state of plants and crop output. Traditional methods only focus on crop growth and its yield. To help landowners, we planned a specialist-based crop observing framework. This examination aims to focus on a specialist-based framework to assist the agriculturists with checking the yields from a distance by utilizing the satellite imaging technique. The framework is separated into principal two fundamental parts. The initial one is information procurement and the other one is the proposal part. The readings of vital ecological boundaries are taken and turned into a simulation. Variety handling procedures are utilized to track down the nitrogen lack in the green plants this technique will give adequate data about future situations of nitrogen content in the plants.